Control of industrial major accident hazard regulation in Malaysia: second decade in examination - Rasyimawati Mat Rashid; Radin Zaid Radin Umar (Intelektual Pustaka Media Utama, 2023)
The Control of Industrial Major Accident Hazards (CIMAH) regulations was introduced in 1996 to regulate workplaces with hazardous chemicals in their facilities. The Regulations provide a minimum standard to ensure precautionary measures related to major hazard risks are taken. Although the Regulations have been enforced for more than two decades in Malaysia, there have been limited efforts to review related information, trends and data since its inception. The study aimed to provide an overview of the position of CIMAH regulations after two decades of being enacted in Malaysia. Data were extracted from the published and unpublished reports and documentations by Department of Occupational Safety and Health of Malaysia (DOSH), as well as available publications from literary journals. Analysis of the contents revealed three categories of data: i) CIMAH regulations’ administrative governance changes; ii) major hazard industries–categorization and registration trends; and iii) CIMAH regulations’ punitive activities. The findings provide an overview of relevant trends and data related to CIMAH regulations in the past two decades, and may provide stakeholders such as policymakers, practitioners, and researchers a groundwork for improvement initiatives.